Sistem Tebas Bakar dan Pengaruhnya Terhadap Komponen Fisik Kimia Tanah Serta Vegetasi pada Ladang dan Lahan Bera (Studi Kasus di Desa Pruda Kecamatan Waiblama Kabupaten Sikka Provinsi Nusa Tenggara Timur) - Henderikus Darwin Beja; W. I.I. Mella; I. N. Prijo Soetedjo (Jurnal Keteknikan Pertanian, 2015)
Shifting cultivation by slash and burn system is an agricultural activity which is generally done farmers in dry land. Slash-and-burn is practiced by the farmers because it is easy and inexpensive, with aims to improve the content of nutrients in the soil, eradicate weeds, reduce costs, reduce the incidence of pests and diseases and to increase crop production. Land clearing by slash and burn system in a short period of time have a positive impact as the availability of N, P, K, Ca, Mg. However, long periods of slash and burn have negative impact there will be changes in physical and chemical components of soil and change the dominant vegetationin the fields and fallow land. These changes will affect the l evel of productivity of the soil, especially in the land which was done. To reduce the negative impacts, farm management system with slash and burn practices, should be considered with conservation activities, especially from the aspect of land management techniques. Those negative effect might be minimized by arious treatments such as time of burning tehnique, chosen of burned biomass, and time of digged biomass. All those should be supported by a basic information affect of burning to change of physical and chemical soil characteristic at various land cultivation and length of cultivation. Result of study that had been conducted at Pruda village, sub-district of Waiblama, district of Sikka, Propince of Nusa Tenggara Timur showed that total Nitrogen and C organic increased gradually when land has been 3 years fallow. Result of single factor showed that soil aggregation was a ffected significantly by fallow than cultivated land .